Process Model of Quality Cost Monitoring for Small and Medium Wood-Processing Enterprises - Denis Jelačić (University of Zagreb, Faculty of Forestry and Wood Technology, 2016)
Quality is not only a technical category and the system of quality management is not only focused on product quality. Quality and costs are closely interlinked. The paper deals with the quality cost monitoring in small and medium wood-processing enterprises (SMEs) in Slovakia, and also presents the results of the questionnaire survey. An empirical study is aimed to determine the level of understanding and level of implementation of quality cost monitoring in wood-processing SMEs in Slovakia. The research is based on PAF model. A suitable model for quality cost monitoring is also proposed in the paper based on the research results with guidelines for using the methods of Activity Basic Costing. The empirical study is focused on SMEs, which make 99.8 % of all companies in the branch, and where the quality cost monitoring often works as a latent management subsystem. SMEs managers use indicators for monitoring the processe performance and production quality, but they usually do not develop a separate framework for measuring and evaluating quality costs.